Impeding green customization: the roles of negative perceptions, environmental responsibility and claim type - Wang, Chen; Zhang, Ran; Feng, Taiwen; Tao, Jingyi (Management decision, 2023)
PurposeThis study aims to investigate the impact of environmental responsibility (ER) on consumers' green customization intention (GCI), as well as the separate and joint moderating effects of consumers' negative perceptions and environmental claim type (ECT) on the relationship between ER and GCI.Design/methodology/approachIn this study, two online experimental questionnaires and one between-subject lab experiment were conducted to test all hypotheses.FindingsThis study found that high-ER consumers are more likely to choose environmental options in the product customization process (versus low ER). The effect of ER on consumers' GCI is moderated by consumers' negative perceptions of green consumption (e.g. green skepticism and perceived environmental premium (PEP)). Additionally, ECT's joint moderating effect and consumers' negative perception of green customization consumption can be decreased by a substantive (versus associative) claim type in message framing.Practical implicationsThe findings provide new insights into the factors affecting consumers' GCIs and have significant practical implications. First, consumers' different ER levels should not be neglected when examining the value of green customization. Second, consumers' green skepticism and PEP could reduce consumers' GCI. Third, the use of substantive environmental claims may also be particularly helpful for companies' communication strategies regarding consumers' low-level negative perceptions of green options.Originality/valueWhile previous studies state “environmental responsibility” as a key characteristic of general green consumption, the authors extend that to a green customization process and connect that with consumers' negative perceptions and ECT. In addition, the separate and joint moderating effects of consumers' negative perceptions and ECT were examined. Thus, these findings refine the existing understanding of the relationship between ER and green customization.